The role of colonoscopy in assessing bleeding in patients with lower gastrointestinal disorders: Pathogenesis and therapeutic applications for patients referred to Al-Hussein Teaching Hospital during the period 2023-2024 - Abdulmuhsen, Faez Khalaf; Abdulhussien, Adeeb Abdulally; Mousa, Hameed Naeem; Al-Jawher, Rasha Qusai; yaseen, lamia jarallah (Journal of Neonatal Surgery, 2025)
Colon gastrointestinal (GI) bleeding is a frequent cause of hospitalization and is more prevalent in the elderly. Patients with persistent bleeding or significant hemorrhage stigmata need immediate diagnosis and intervention to ensure permanent hemostasis, even though the majority of instances will stop on their own. The main method for diagnosing, assessing risk, and treating some of the most frequent causes of colonic bleeding—including diverticular hemorrhage, which accounts for 30% of cases—is colonoscopy. Surgery and angiography are typically saved for cases of bleeding that are uncontrollable or do not permit sufficient intestinal preparation for a colonoscopy. In patients who arrive with severe hematochezia, we go over the colonoscopic diagnosis, risk assessment, and final therapy of colonic bleeding. Objective : Al-Hussein Teaching Hospital in Al-Nasiriyah city, Thi-Qar governorate, evaluated lower gastrointestinal bleeding patients in 2023–2024 and the usefulness of colonoscopies. Methods: The investigation was conducted in the endoscope department of an Al-Hussian teaching hospital next to a medical college. the Southern Iraqi Dhi-Qar Governorate from July 2023 and March 2024. Patients with lower git hemorrhage, with or without an alert feature, were assessed for this hospital-based observation research. 150 individuals had lower gastrointestinal endoscopies. Males were 95 (63.3) and females were 55 (36.6), the most prevalent age group between 21 and 60. Results: Internal hemorrhage (18.6%), poor preparation (12.6%), ulcerative colitis (9.2%), internal pill (8.6%), rectal mass (7.9%), proctitis (4.6%), polyp (3.39%), and rectal ulcer (2%) were among the colonoscopy results, which included normal (28.5%). When an internal hemorrhage is discovered during a colonoscopy, the majority of patients report 10 percent bleeding per rectum, 4 percent stomach discomfort with bleeding per rectum, 2 percent painless bleeding, 2 percent blood per rectum with mucus, 6 percent recurrent bleeding per rectum, and 6 percent intermittent bleeding per rectum. Conclusion : Between the ages of 21 and 60, lower gut bleeding is widespread, with internal hemorrhoids being the most frequent source of bleeding per rectum. A colonoscope is a device that option for both diagnosis and treatment. Successful results will be obtained by using the right tools, techniques, and knowledge. radiological intervention and When a colonoscopy fails to diagnose or achieve sufficient hemostasis, surgery is the last resort. Categories: General Surgery, Gastroenterology